1995
DOI: 10.1007/bf01691496
|View full text |Cite
|
Sign up to set email alerts
|

Monoclonal antibodies againstHaemophilus ducreyi lipooligosaccharide and their diagnostic usefulness

Abstract: Mouse monoclonal antibodies (MAbs) DP8 [immunoglobulin G1()] and DH24 [immunoglobulin M()], which are specific for Haemophilus ducreyi lipopolysaccharide (LPS), were generated by fusing mouse myeloma NS0 cells with spleen cells of BALB/c mice immunized with a total membrane preparation of H. ducreyi. MAb DP8 reacted in whole-cell enzyme immunoassay (EIA) and colony dot immunoblotting with all 50 strains of H. ducreyi but not with any other bacteria tested, which suggests an exposed and species-specific epitope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 36 publications
1
14
0
Order By: Relevance
“…However, the involvement of the toxin in the pathogenesis of chancroid has not yet been shown. Both in the temperature-dependent rabbit model and in the human model for chancroid, H. ducreyi strains with a mutation in the CDT genes were shown to be as virulent as their isogenic parent strains [34,35]. However, these models do have limitations; animal cells are known to be not sensitive or less sensitive to HdCDT than human cells and, therefore, the pathogenesis in these rabbits could be different from that in man.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the involvement of the toxin in the pathogenesis of chancroid has not yet been shown. Both in the temperature-dependent rabbit model and in the human model for chancroid, H. ducreyi strains with a mutation in the CDT genes were shown to be as virulent as their isogenic parent strains [34,35]. However, these models do have limitations; animal cells are known to be not sensitive or less sensitive to HdCDT than human cells and, therefore, the pathogenesis in these rabbits could be different from that in man.…”
Section: Discussionmentioning
confidence: 99%
“…The identities of all H. ducreyi strains were con®rmed by a modi®ed version of a previously described PCR assay [34]. The primers used were the H. ducreyi 16S rRNA-speci®c sequence RPI 59-CCCCTTTGCAGG TTTGCCGCCCTC-3 9 , positions 1207±1230 and the non-speci®c sequence U3 59-GTGCCTGCAGCCGC GGTAAT-3 9 , corresponding to base positions 515±534 of the highly conserved U3 region of Escherichia coli 16S rRNA, to amplify a 758-bp fragment.…”
Section: Pcrmentioning
confidence: 99%
“…[33][34][35] This hypothesis is supported by observations that the use of additional confirmatory PCR assays, designed to amplify different DNA targets to the first PCR assay, were able to resolve discrepant PCR positive culture negative results. 35 37 Virtually all the discrepant results were positive in the confirmatory PCR 42 By using PCR as the reference standard, the IF test was shown to have a sensitivity of 100% and a specificity of 74% in comparison with culture and a sensitivity of 89% and a specificity of 81% in comparison with the PCR assay. The authors reported that their MAb based IF assay was superior to bacterial culture which means that it may be a good candidate for use in diagnostic tests in high chancroid prevalence populations.…”
Section: Dna Amplification Techniquesmentioning
confidence: 98%
“…The species specificity of all isolates was confirmed by PCR, developed and evaluated previously (1,3). The primers used to amplify the 758-bp fragment were the H. ducreyi 16S rRNA-specific sequence 5Ј-CCCTTTGCAGGTTTGCCGCCCTC-3Ј and the nonspecific sequence U3 (5Ј-GTGCCTGCAGCGCGGTAAT-3Ј), which was derived from the highly conserved U3 region of Escherichia coli 16S rRNA.…”
Section: Bacterialmentioning
confidence: 99%
“…Structurally defined epitopes of 10 H. ducreyi LOSs have been studied using monoclonal antibodies (MAbs). The MAb MAHD6 recognizes an epitope that is present only in the pentasaccharide branch of LOS, which suggests the possibility of distinguishing between two phenotypic groups of isolates, based on the expression of long and short LOS (1,2).…”
mentioning
confidence: 99%